Perspectives For the Development of Transport In Romania by 2050 - Frantz Daniel FISTUNG; Cornelia NEAGU; Marius BULEARCA; Cristian SIMA (Communications of International Proceedings, 2024)
This study aims to present the new trends in the development of transport in Romania, and mainly of the specific infrastructure network, in the context of the growing demands for sustainable development of the society and the inadequate situation of transport caused by past and current errors induced by the Romanian authorities in this area. As a member of the common transport market within the EU, Romania needs to experience a paradigmatic change in the transport sector’s development strategy by taking all the necessary measures to achieve the sustainable mobility target. Unfortunately, this goal is difficult to achieve both due to the inertia of policies developed in the past in this economic sector, but unfortunately also due to the instability generated by the inconstancy of the vision and the maintenance of the development objectives of the transport system in Romania. The inadequate situation of the national transport network was the main factor that led to diminishing the opportunities offered by Romania’s geo-political position. Energy consumption in the sector is increasing, causing huge environmental damage and especially in the production of greenhouse gases. Things can no longer continue in this way and therefore, the authors of the current study propose a series of measures aimed at leading to a profound change in the orientation of Romanian transport towards an accessible, efficient and protective sector in relation to the environment and the health of living creatures. The study is based on analyses of data related to urban localities on both national and international plans.
Keywords: Transport; Sustainable Mobility; Transport Policies